Deteksi Dini Resiko Tinggi Pada Ibu Hamil melalui program “Kemilau Penari”gi Pada Ibu Hamil melalui program “Kemilau Penari” - Wuri Widi Astuti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Pregnancy is a physiological condition and has great meaning in every woman's life. Although it is physiological in nature, the presence of diseases previously suffered by pregnant women or complications during pregnancy can cause complications for both the mother and the fetus in the womb. Therefore, it is necessary to make efforts to improve health, especially for pregnant women by detecting complications and high risks in pregnancy. The purpose of this activity is to improve education for pregnant women about early detection of high risks and complications in pregnancy by carrying out community service activities with the "Green Dancer" program. The target is 15 pregnant women TM III which will be held from 07-13 June 2022 at PMB Hj. Karwati, SST., BD Ngampel Village, Mojoroto District, Kediri City. The activity was carried out through 3 stages, namely the pre-test stage which aims to determine the extent of knowledge and understanding of high-risk mothers in pregnant women. The second stage is providing material on high risk early detection and how to assess risk scores using KSPR. The third stage is to evaluate the participants regarding the material that has been given by giving a post test and ending with the formation of a discussion group via Whatsapp. The results of the activities from the counseling were found that most of the mother's knowledge increased in the good category. Pregnant women can fill out and read scores in the KSPR, as well as form an educational group with the name 3K ON. With this innovation, it is hoped that it can help overcome the problems of pregnant women related to complications and can contribute to the reduction of MMR and IMR.